Application of Fenton’s Reaction for Removal of Organic Matter from Groundwater - Krupińska, Izabela (Molecules, 2024)
In this study, the effectiveness of the Fenton process in removing natural organic matter (NOM) from groundwater was investigated. The subject of this study is groundwater characterised by increased content of NOM and iron (II) compounds. In laboratory-scale studies, the influence of the ratio of concentrations of Fe(II) ions, which are naturally occurring in groundwater, to hydrogen peroxide (H2O2) as well as oxidation time and pH on the removal efficiency of organic matter was determined. Indicators such as total organic carbon (TOC), dissolved organic carbon (DOC), UV absorbance at 254 nm (UV254), UV absorbance at 272 nm (UV272), and specific UV absorbance (SUVA254) were used to quantitatively and qualitatively assess the organic substances present in the raw water and after oxidation with Fenton’s reagent. Analysis of the results obtained showed that the highest removal efficiency of organic substances in the deep oxidation process using the Fenton reaction was obtained for a concentration ratio of Fe(II) to H2O2 = 1:5. Acidification of the water samples to a pH of about 4 and extending the oxidation time to 30 min significantly increased the removal efficiency of organic substances including mainly dissolved organic substances containing aromatic rings. The organic substances containing aromatic rings, determined at a wavelength of 254 nm, were degraded to other organic intermediates.